PENGARUH TINGKAT PARTISIPASI ANGKATAN KERJA, TINGKAT PENGANGGURAN TERBUKA DAN TINGKAT PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI ACEH - Rezki Maulana; Cut Zakia Rizki; Fitrah Afandi ZT (Fakultas Ekonomi dan Bisnis UNSYIAH, 2023)
AbstractThis study aims to analyze how the influence of the labor force participation rate, unemployment rate, and education level on economic growth in Aceh Province. The data used in this study is secondary data, namely panel data consisting of 23 districts/cities in Aceh Province from 2015 to 2020. The method used is panel data regression with the Fixed Effect Model (FEM). The results of this study indicate that the open unemployment rate and education level partially have a significant effect on economic growth in Aceh Province, labor force participation rate has not partially affected economic growth in Aceh Province. As a government can improve the quality and quantity at the education level to be better, the government can adopt policies that can increase employment so that there is no increase in the unemployment rate, especially in Aceh Province. It is hoped that the government can carry out more in-depth supervision of the program to overcome problems at the education level and unemployment rate in order to create better economic growth in Aceh Province.Keywords : Economic Growth, Labor Force Participation Rate, Unemployment Rate, Education Level.